Comparison of mathematical methods for the evaluation of wastewater settleability by settling column tests. Issue 6 (19th March 2017) - Carbone, Marco; Penna, Nadia; Piro, Patrizia
ABSTRACT: Particulate matter (PM), which may serve as a vector of pollutants in both natural and human-impacted waters, is of primary interest in water quality studies, particularly for those conducted in urban areas. Separating solids from the liquid phase is one of the main goals of water treatment practices. Above all, the settling process is the most commonly used for this purpose. Generally, settling column tests are used in the laboratory to assess the total PM removal. Besides the traditional graphical method used for the interpretation of the laboratory results, other mathematical methods were developed – with the goal of simplifying the settling efficiency evaluation procedure and making it less subjective. To make a contribution in that direction, a study based on the comparison of four different mathematical methods for estimating PM removal efficiencies was conducted. The analysis was carried out on 15 samples of wastewater and showed that only two methods gave satisfactory results, and only one of them was physically based. Consequently, it is recommended to assess the overall PM removal, E tot, by a monoparametric exponential function, depending on the settling time ( t ) and on the first-order decay coefficient ( k ).